2018
DOI: 10.1155/2018/1648017
|View full text |Cite
|
Sign up to set email alerts
|

Absent Audiovisual Integration Elicited by Peripheral Stimuli in Parkinson’s Disease

Abstract: The basal ganglia, which have been shown to be a significant multisensory hub, are disordered in Parkinson's disease (PD). This study was to investigate the audiovisual integration of peripheral stimuli in PD patients with/without sleep disturbances. Thirty-six age-matched normal controls (NC) and 30 PD patients were recruited for an auditory/visual discrimination experiment. The mean response times for each participant were analyzed using repeated measures ANOVA and race model. The results showed that the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The statistical significance level was set at P ≤ 0.05, and the effect size (η P 2 ) estimates were reported. Identical to our previous studies (Ren et al, 2016(Ren et al, , 2018a, the AVI effect was assessed using the race model behaviorally. The independent race model is a statistical prediction model based on the cumulative distribution functions (CDFs) of the summed probabilities of the visual and auditory responses to independent unimodal visual and auditory stimuli (Miller, 1982(Miller, , 1986.…”
Section: Behavioral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical significance level was set at P ≤ 0.05, and the effect size (η P 2 ) estimates were reported. Identical to our previous studies (Ren et al, 2016(Ren et al, , 2018a, the AVI effect was assessed using the race model behaviorally. The independent race model is a statistical prediction model based on the cumulative distribution functions (CDFs) of the summed probabilities of the visual and auditory responses to independent unimodal visual and auditory stimuli (Miller, 1982(Miller, , 1986.…”
Section: Behavioral Datamentioning
confidence: 99%
“…Because the AVI effect calculated based on the race model was statistical facilitation cross all participants (Miller, 1982(Miller, , 1986, and it is unable to calculate the AVI effect of individual participant. Therefore, the multisensory response enhancement (MRE) here was introduced through the index (ii) to evaluate the AVI effect of each individual, and further to study the relationship between the AVI effect and theta and alpha activity (Stevenson et al, 2014;Ren et al, 2018a). The MRE is the response gain attributable to having information from a second sensory modality available (Stein and Meredith, 1993).…”
Section: Correlation Analysismentioning
confidence: 99%
“…It has been demonstrated that the basal ganglia play a pivotal role in this integration process [52]. As basal ganglia undergo considerable structural changes due to loss of dopaminergic neurons in substantia nigra in PD [1] it is not surprising that PD patients have difficulties in multisensory integration processes [53][54][55]. Accordingly, following the results of the present study, we assume that the degeneration of dopaminergic neurons in the basal ganglia results in a modified integration process of the facial feedback that potentially explains the lack of influence of facial feedback on emotional change detection in PD.…”
Section: Discussionmentioning
confidence: 99%
“…For all subjects, the probability difference curves were average to obtain the mean probability difference curves. The greatest audio–visual facilitation of the mean probability difference curves is defined as peak benefit, and the time spanned from the presentation of the target to the maximal benefit is defined as the peak latency, which was used to assess the time point when AVI occurred together with the time window of AVI as in previous study (Diederich et al., 2008; Ren, Suzuki, et al, 2018; Ren, Yang, Nakahashi, Takahashi, & Wu, 2016). Besides, the individual peak latency was also obtained from probability difference curve, and the statistical analysis of significance between elderly and younger adults was conducted basing on the individual peak latency (two‐tailed t test, p ≤ .05).…”
Section: Methodsmentioning
confidence: 99%